2021
DOI: 10.1038/s42003-021-02031-2
|View full text |Cite
|
Sign up to set email alerts
|

Environmental DNA provides higher resolution assessment of riverine biodiversity and ecosystem function via spatio-temporal nestedness and turnover partitioning

Abstract: Rapidly assessing biodiversity is essential for environmental monitoring; however, traditional approaches are limited in the scope needed for most ecological systems. Environmental DNA (eDNA) based assessment offers enhanced scope for assessing biodiversity, while also increasing sampling efficiency and reducing processing time, compared to traditional methods. Here we investigated the effects of landuse and seasonality on headwater community richness and functional diversity, via spatio-temporal dynamics, usi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 65 publications
4
43
1
Order By: Relevance
“…The study of diversity on a regional scale (gamma diversity) shows the ability of environmental DNA to detect many taxa also identified by the traditional kicknet method. This result is in line with previous studies which reported several EPT taxa detected by both methods (Mächler et al 2019, Seymour et al 2021). However, a significant number of taxa known to be present in these rivers (according to the kicknet sampling) could not be detected by either the mlCOIintF/HCO2198 or fwhF2/EPTDr2n primers.…”
Section: Discussionsupporting
confidence: 93%
“…The study of diversity on a regional scale (gamma diversity) shows the ability of environmental DNA to detect many taxa also identified by the traditional kicknet method. This result is in line with previous studies which reported several EPT taxa detected by both methods (Mächler et al 2019, Seymour et al 2021). However, a significant number of taxa known to be present in these rivers (according to the kicknet sampling) could not be detected by either the mlCOIintF/HCO2198 or fwhF2/EPTDr2n primers.…”
Section: Discussionsupporting
confidence: 93%
“…Inferrering community ecological indices from metabarcoding data can be relatively straightforward to adapt, at least from an analysis standpoint. Taxon richness can be easily calculated from metabarcoding data (Seymour et al 2021), while abundance based indices, including Shannon and Simpson indices, can be derived by calculating Hill numbers from relative read abundances using an index based approach to existing statistical methods (Chao et al 2014, Alberdi and.…”
Section: Text Box 3: Ecological Indices Inferred From Metabarcodingmentioning
confidence: 99%
“…A two-step PCR-based library preparation protocol was performed after initially optimizing the PCR methods, based on the two-step adapter system outlined by Miya et al, 2015 andothers (e.g., Brennan et al, 2019;Holman et al, 2021;Seymour et al, 2021). In summary, each biological replicate was prepared as a single library; thus, three libraries resulted from each site for each sampling event.…”
Section: Pcr-based Library Preparationsmentioning
confidence: 99%
“…Distribution data for fishes, which are among the most well-studied marine species, are often based on catch data from commercial fishing practices or ecological studies, which can be biased toward certain species and highly dependent on sampling strategy and timing (Boenish et al, 2020;Pope et al, 2010). As such, traditional methods can limit biodiversity surveys both temporally and spatially, where data cannot be systematically collected and compared (McElroy et al, 2020;Seymour et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation